Microbiological risk assessment of microwave heating on ready-to-eat foods - New, Chia Yeung (2017)
The microwave oven is an inexpensive multifunctional device commonly used for reheating purpose during meal preparation. The safety level of microwave heated foods remains in vague due to consumers’ lack of awareness and knowledge on microwave heating the food safely. This research study aimed to scientifically address the microbiological safety of microwave heated ready-to-eat (RTE) foods. To initiate the study, a consumer survey study was conducted to measure the Malaysian’s consumers’ knowledge and practice microwave oven safety. Next, the survivability of Salmonella enterica and Shiga-toxigenic Escherichia coli (STEC) O157 in microwave heated RTE foods was studied to identify the risk factors and subsequently evaluate the risk factors. The prevalence of the foodborne pathogens’ survivability in microwave heated RTE foods was investigated using the Most Probable Number coupled Polymerase Chain Reaction (MPN-PCR) method. The highest possibility of the foodborne pathogens’ survival was due to factors affecting the microwave heating in particular presence of cold spots, microwave heating time and consumers’ knowledge; all identified as risk factors. In the food safety context, microwave heating time and consumers’ knowledge was given more attention. The microwave heating time on the influence of different food composition in relation to bacteria inactivation was then studied and the data was used to model the bacterial inactivation using the Weibull model. These studied risk factors were then incorporated into a retail and consumer phase exposure assessment model to estimate the risk of consumption of contaminated RTE food reheated at different microwaving times using @risk. The outcome of the study showed that the respondents demonstrated low level of knowledge and safety practice of the microwave oven, although they had neutral attitude on food safety. Out of the 329 samples of various convenience meals collected around Wilayah Persekutuan Kuala Lumpur and Selangor regions, 20.1% were tested positive with Salmonella spp. and 5.2% with STEC O157. Fats were observed to have the highest influence to the microwave heating time compared to proteins and carbohydrates. Based on the overall food composition, the results indicated that the foodborne pathogens were fully inactivated by microwave heating at 60 seconds as no viable growth was observed. However, the risk assessment model estimated probable foodborne illness cases for RTE food microwave heated less than 90 seconds for S. enterica serovar Enteritidis and STEC O157 exposure assessment models. The outcome indicated that RTE food should be microwave heated up to 90s and more to ensure the safety of the food and other interventions such as controlling the holding temperature and having a fixed display holding time. The current risk research study provided comparative information on the evaluation of microwave technology in terms of food safety. Notably, foodborne pathogens can survive the microwave heating which put the consumers at risk when improper safety practice and usage of the microwave oven is taken. The implementation of microwave heating guidelines, involving the safe microwave heating time and safety practice, into food safety educational programs should be established as risk interventions and further to conserve the public health.